v=12⋅(pr2h)

Rewrite the equation as 12⋅(pr2h)=v.

12⋅(pr2h)=v

Multiply both sides of the equation by 2.

2⋅12⋅(pr2h)=2⋅v

Cancel the common factor of 2.

Cancel the common factor.

2⋅12⋅(pr2h)=2⋅v

Rewrite the expression.

1⋅(pr2h)=2⋅v

1⋅(pr2h)=2⋅v

Multiply pr2h by 1.

pr2h=2⋅v

pr2h=2v

Divide each term in pr2h=2v by pr2.

pr2hpr2=2vpr2

Simplify pr2hpr2.

Cancel the common factor of p.

Cancel the common factor.

pr2hpr2=2vpr2

Rewrite the expression.

r2hr2=2vpr2

r2hr2=2vpr2

Cancel the common factor of r2.

Cancel the common factor.

r2hr2=2vpr2

Divide h by 1.

h=2vpr2

h=2vpr2

h=2vpr2

h=2vpr2

Solve for h v=1/2*(pr^2h)